A shared promoter region suggests a common ancestor for the human VCX/Y, SPANX, and CSAG gene families and the murine CYPT family - Hansen, Martin A.; Nielsen, John E.; Retelska, Dorota; Larsen, Niels; Leffers, Henrik (Molecular reproduction and development, 2008)
Many testis‐specific genes from the sex chromosomes are subject to rapid evolution, which can make it difficult to identify murine genes in the human genome. The murine CYPT gene family includes 15 members, but orthologs were undetectable in the human genome. However, using refined homology search, sequences corresponding to the shared promoter region of the CYPT family were identified at 39 loci. Most loci were located immediately upstream of genes belonging to the VCX/Y, SPANX, or CSAG gene families. Sequence comparison of the loci revealed a conserved CYPT promoter‐like (CPL) element featuring TATA and CCAAT boxes. The expression of members of the three families harboring the CPL resembled the murine expression of the CYPT family, with weak expression in late pachytene spermatocytes and predominant expression in spermatids, but some genes were also weakly expressed in somatic cells and in other germ cell types. The genomic regions harboring the gene families were rich in direct and inverted segmental duplications (SD), which may facilitate gene conversion and rapid evolution. The conserved CPL and the common expression profiles suggest that the human VCX/Y, SPANX, and CSAG2 gene families together with the murine SPANX gene and the CYPT family may share a common ancestor. Finally, we present evidence that VCX/Y and SPANX may be paralogs with a similar protein structure consisting of C terminal acidic repeats of variable lengths. Mol. Reprod. Dev. 75: 219–229, 2008. © 2007 Wiley‐Liss, Inc.